(untitled) (European Journal of Economics, Finance and Business Development, 2025)
The dynamics of key indicators determining the efficiency of investment funds have been analyzed. Issues of ensuring a favorable investment environment in our country and further increasing the influx of foreign capital have been discussed. Additionally, factors influencing the attraction of foreign investments and the global experience in addressing them have been studied.